Motivation of Phraseological Units Related to French and Uzbek Traditions - Bahodirovna, Djalilova Dilfuza (International Journal on Orange Technologies, 2023)
This article is devoted to phraseology, section of linguistics which examines the motivation of phraseological units representing the customs and traditions of the French and Uzbek peoples.